FLUID COMPOSITIONS IN EQUILIBRIUM WITH SILICA-UNDERSATURATED MAGMAS IN THE SYSTEM NA2O-AL2O3-SIO2-H2O: CLUES TO THE COMPOSITION OF FENITIZING FLUIDS - Preston R.F.; Stevens G.; McCarthy T.S. (My University, 2003)
Fenites result from alkali metasomatism of granitoid rocks associated with the intrusion of silica-undersaturated alkaline magmas, and are characterized by addition of alkalis, iron and magnesium, albitization, nephelinization, removal of silica and the formation of alkali pyroxenes and amphiboles. In an attempt to constrain the fluid compositions involved in this process, we have investigated the compositions of the fluids in equilibrium with a range silica-undersaturated alkaline magmas, in the model system Al2O3-Na2O-SiO2-H2O at 850 °C and 1 kbar. The starting compositions straddle the nepheline-albite join, and include both peralkaline and alkali-granitoid compositions. The quenched run products all contained a glass, representing the melt, as well as an aqueous fluid and a radial crystalline phase interpreted to be a fluid quench phase. Several of the glasses also contained albite, nepheline or quartz crystals. Fluid compositions in crystal-free experiments were calculated using a mass-balance approach that incorporated the composition of the glass, composition of starting materials and carefully determined masses of the different run product fractions, as well as that of the starting materials. Compositions plotting to the peralkaline side of the nepheline-albite join produced fluids that were highly enriched in dissolved solids (SiO2 + Al2O3 + Na2O, in the range 40-50 wt%). This substantial fractionation of the solid starting materials, between melt and fluid phase, results in reasonable resolution of the fluid compositions produced, despite significant uncertainties in the measured Na2O and H2O concentrations in the glasses. Model calculations indicate that the fluid compositions in equilibrium with the more SiO2 undersaturated melt compositions in this study are capable of converting a typical granodiorite to a nepheline syenite composition at fluid/rock ratios lower than 1:1. Albitization and the removal of quartz (in the form of soluble sodium metasilicate), formation of sodic pyroxenes (acmite) and ultimately nepheline are characteristic of the process modeled here. These are largely analogous to the general features observed in some natural fenites.